2000
DOI: 10.1136/bjo.84.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Pain relief with intracameral mepivacaine during phacoemulsification

Abstract: )) while remaining unchanged in the placebo group (2.9 (2.6-3.2) v 2.9 (2.5-3.3)), the mean reduction in pain score being significantly diVerent between the two groups (p<10 −4 ). There was no indication of increased postoperative ocular inflammation, intraocular pressure change, or endothelial cell loss. Conclusions-These results suggest that it may not be necessary to systematically add intracameral anaesthesia with topical anaesthesia for cataract surgery. An intraoperative intracameral injection, performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
(9 reference statements)
0
14
1
Order By: Relevance
“…This drug is also used topically and intracamerally in humans during cataract surgery or other ocular procedures and provides adequate desensitization of the cornea. 30,31 Although there was a reduction in corneal sensitivity following ocular application of mepivacaine solution in the horses in the present study, the anesthetic effect of this treatment was not as notable as that provided by application of each of the other anesthetic agents. The comparatively decreased efficacy of mepivacaine is most likely related to its poor corneal permeability, as shown in rabbits.…”
Section: Discussioncontrasting
confidence: 54%
“…This drug is also used topically and intracamerally in humans during cataract surgery or other ocular procedures and provides adequate desensitization of the cornea. 30,31 Although there was a reduction in corneal sensitivity following ocular application of mepivacaine solution in the horses in the present study, the anesthetic effect of this treatment was not as notable as that provided by application of each of the other anesthetic agents. The comparatively decreased efficacy of mepivacaine is most likely related to its poor corneal permeability, as shown in rabbits.…”
Section: Discussioncontrasting
confidence: 54%
“…Reversible cellular swelling could be observed when the concentration was at least 1 % [40], with permanent damage only at 2 % [38]. Clinical and experimental studies on human corneas confirmed these results, at least for lidocaine [21,25,40,43,54,55] and mepivacaine [52]. Other compounds, like bupivacaine, seem more toxic [3].…”
Section: Safetymentioning
confidence: 58%
“…It has been employed at the 0.50 %, 0.75 % and 2 % concentrations as topical anaesthetic for cataract surgery [17,45,52], showing low corneal epithelium toxicity. The intraocular penetration is good because bupivacaine is extremely liposoluble.…”
Section: Bupivacainementioning
confidence: 99%
See 2 more Smart Citations